Suara Kenabian: Titik Temu Semitic Religion Dalam Membangun Kerukunan Antar Umat Beragama - Lutfi, Achmad; Khairullah, Khairullah (BINA' AL-UMMAH, 2021)
Doctrine, belief, or a set of norms and teachings of God brought by the Prophet are universal and absolute truth. But when it reaches to the practice stage of its adherents, it will be intertwined with the quality of understanding and appreciation that are relative, for every appreciation cannot be separated from certain socio-cultural settings that surround its adherents. Basically, the divine religions are allied religions that have historical roots and teaching substance  which is not different, so that at the level of application it should not give birth to different patterns of appreciation and patterns of social behavior. This paper will discuss whether there is a meeting point for the diversity of views and religious understandings brought by the prophets of the heavenly religion, and how the relationship between these views is in an effort to build harmony between religious communities.